Necessary and sufficient condition for robust stability of discrete-time descriptor polytopic systems - Gao, X.; Teo, Kok Lay; Duan, G.; Zhang, X. (Stuart Govan, Institution of Engineering and Technology, 2011)
This study investigates the robust stability of discrete-time descriptor polytopic systems. Necessary and sufficient conditions for robust stability expressed as parameterised linear matrix inequalities (LMIs) are obtained. Furthermore, the parameterised LMIs are reduced to parameter-independent and finite-dimensional LMIs. Finally, two numerical examples are given, illustrating the effectiveness of the proposed method.